Determinant Factors of Sports Achievement of State Senior High School Students Special for Sports Gifted South Sulawesi - Abriadi Muhara; Husain Syam; Abdullah Sinring (Jurnal Multidisiplin Madani, 2022)
Education is important in global life because it determines the quality of human resources. Education in Indonesia has begun to focus on providing educational services for children with above average intelligence through the Special Talent Education (PBI) program, which will contribute to the honor and reputation of the Indonesian nation among other nations in the world. This study intends to determine the effect of achievement motivation, self-efficacy, self-regulation, school environment, and social support on sports achievement of South Sulawesi State High School Special Gifted Students. The research method is quantitative with this type of correlational research and ex-post facto design. Data collection techniques were carried out by documenting primary sports achievement data and giving questionnaires to students. Descriptive data analysis, multiple linear regression requirements test, and hypothesis testing are the data analysis techniques used. This study found a significant influence between achievement motivation, self-efficacy, self-regulation, school environment, and social support, both partially and simultaneously, on the sports achievement of South Sulawesi State High School Specialized Sports Talent students. Finally, this study provides input for the future to continue sports achievement research which has aspects of self-regulation and the school environment as well as social support without excluding other variables that can affect the increase in sports achievement and student academic achievement